Travel of Bonpo Gods from the Eurasian Borderlands to theTibetan Culture Area and the Borderlands of North-eastIndia (Kawalu: Journal of Local Culture, 2024)
Popular portrayals often depict Hindu deities as exclusive to Hinduism, viewed primarily as a religion of the Indian subcontinent. However, this perspective oversimplifies Hinduism, ignoring the significant exchange of gods and beliefs with other religions. This challenges the idea of Hinduism as a closed system and raises difficulties in defining it, as no single definition exists. Pre-modern India had extensive cultural exchanges with Central and Southeast Asia, evident in religion and culture. Nationalist and Eurocentric histories have shaped modern views, often ignoring earlier influences and portraying religions like Hinduism and Buddhism as homogenous. For instance, in Sri Lankan Buddhist temples, one can still find Hindu deities like Ganesha and Karthikeya, highlighting the fluidity of religious boundaries.